Technical Factor Analysis that Impacts Building Maintenance in the Retention Phase - Ramadhani, Achmad Nur; Putra, I Nyoman Dita Pahang (Civil and Sustainable Urban Engineering, 2026)
Building maintenance during the retention phase (Defects Liability Period) was a critical stage in construction projects because defects frequently emerged after handover and could cause delays, cost overruns, and disputes between owners and contractors. In Indonesia, although a retention fund mechanism was applied, maintenance performance during this phase often remained suboptimal. This study aimed to identify and quantify the influence of technical factors on building maintenance success in high-rise projects during the retention phase in Surabaya. Data were collected through a structured questionnaire using a five-point Likert scale from 31 project staff members with relevant professional experience, selected using purposive sampling. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate both the measurement and structural models, supported by supplementary regression analysis. The results showed that technical factors had a strong and significant effect on building maintenance success, with material availability emerging as the most influential technical factor, while schedule planning was the most dominant success criterion. The high R² and effect size values indicated that technical factors played a substantial practical role in determining maintenance performance during the retention phase. These findings highlighted the importance of effective material logistics, systematic maintenance planning, and strict quality control. Overall, the study demonstrated that improved technical management practices significantly enhanced maintenance performance. From a practical perspective, contractors were encouraged to establish stockpiles of essential materials and adopt digital tools for maintenance planning to ensure timely execution, smooth operations, and effective cost control during the retention phase.